1998
DOI: 10.2135/cropsci1998.0011183x003800060036x
|View full text |Cite
|
Sign up to set email alerts
|

Root Archutecture Affects Nitrate Leaching from Bentgrass Turf

Abstract: Understanding the determinants of nitrate leaching should improve nitrogen uptake efficiency and reduce ground water contamination. This column lysimeter study examined the effect of root architecture on NO3 leaching from two genotypes of creeping bentgrass (Agrostis palustris Huds.) differing in rooting characteristics. Ammonium nitrate was applied (50 kg N ha−1) and the columns were irrigated with 1, 2 or 3 cm day−1 (Exp. 1) or irrigation was delayed 1, 3 or 5 d (Exp. 2). In Exp. 1, leachate NO3 concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 0 publications
5
81
1
Order By: Relevance
“…These data are consistent with previous results on tall fescue (Bowman et al, 2000) and bermudagrass (Green et al, 1997), and demonstrate that N uptake by bermudagrass turf is not significantly reduced by moderate salinity. Healthy turfgrasses are extremely efficient at absorbing N due both to a high uptake capacity (Bowman et al, 1989) and an extensive root system (Bowman et al, 1998). The results of this and our previous study with tall fescue indicate that both warm-and cool-season turfgrasses maintain high N uptake efficiency under conditions of moderate rootzone salinity.…”
Section: Nitrate Leachingsupporting
confidence: 52%
“…These data are consistent with previous results on tall fescue (Bowman et al, 2000) and bermudagrass (Green et al, 1997), and demonstrate that N uptake by bermudagrass turf is not significantly reduced by moderate salinity. Healthy turfgrasses are extremely efficient at absorbing N due both to a high uptake capacity (Bowman et al, 1989) and an extensive root system (Bowman et al, 1998). The results of this and our previous study with tall fescue indicate that both warm-and cool-season turfgrasses maintain high N uptake efficiency under conditions of moderate rootzone salinity.…”
Section: Nitrate Leachingsupporting
confidence: 52%
“…Larger plants were associated with more effective removal of P into biomass, reduced volume of leachate and reduced total P in leachate. Previous work has shown that plants with higher root length densities in the absence of AM colonization and deeper root distribution could capture more nitrate and decrease nitrate leaching from the soil profile than plants with lower root densities and shallow distribution (Bowman et al, 1998;Dunbabin et al, 2003). Similar information has not previously been provided for P. In our experiments increased surface area of the roots of T. subterraneum as a result of AM fungal colonization may have led to increased P uptake, but no effects were found when the P level supplied was sufficient for maximum growth.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, higher uptake of 15 N by juvenile Panicum from the pulsed treatments (NP and NWP) represents an adaptation to acquire resources when episodically available (Cui and Caldwell 1997;Ehleringer et al 1999). High root:shoot ratio (Derner and Briske 1999;Campbell and Grime 1992), and SRL (Silverbush and Barber 1983;Bowman et al 1998;Sullivan et al 2000) increased the capacity for juvenile Panicum to use pulses of nitrogen and water (NP and NWP treatment). Higher root length per unit mass (SRL) and significantly lower root diameters lead to a greater absorptive surface area and potentially greater capacity for N uptake.…”
Section: Pulsed Resource Utilization and Plant Agementioning
confidence: 99%